Students' Mathematical Misconceptions on Circular Material Using Five-Tier Diagnostic - Yandi Heryandi; Aega Amalia (Educational Insights, 2025)
In this research, using the Five-Tier Diagnostic Test aims to determine the level of students' ability in solving HOTS type questions on circle material, find out the types of students' mathematical misconceptions in solving HOTS type questions on circle material, and find out the factors that can cause mathematical misconceptions. student. This research method is descriptive quantitative with a case study research design on class VIII students of SMPN 1 Gunung Jati, where the research is more focused on analyzing students' mathematics misconceptions. Data collection techniques include tests and interviews. Meanwhile, data analysis techniques use interactive models. The research results showed that the level of students' ability in solving HOTS type questions on circle material was in the category of understanding the concept, not understanding the concept, and misconceptions. The types of misconceptions experienced by students are correlational misconceptions, classificational misconceptions, and theoretical misconceptions. Internal factors can be caused by students themselves, because students do not try to repeat learning, do not study sources other than the school handbook, and do not try to practice questions other than those given by the teacher. Meanwhile, external factors can come from teachers, textbooks and learning media.